2008
DOI: 10.1007/s11671-008-9121-9
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Poly(methyl methacrylate) Brushes from Magnetite Nanoparticles Using a Phosphonic Acid Based Initiator by Ambient Temperature Atom Transfer Radical Polymerization (ATATRP)

Abstract: Poly(methyl methacrylate) in the brush form is grown from the surface of magnetite nanoparticles by ambient temperature atom transfer radical polymerization (ATATRP) using a phosphonic acid based initiator. The surface initiator was prepared by the reaction of ethylene glycol with 2-bromoisobutyrl bromide, followed by the reaction with phosphorus oxychloride and hydrolysis. This initiator is anchored to magnetite nanoparticles via physisorption. The ATATRP of methyl methacrylate was carried out in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
1
46
1
Order By: Relevance
“…Even though not many comparable data are available in the literature on this point, these densities are relatively high comparing to similar studies reported. In particular, Garcia [20], and Babu and Dhamodhran obtained 2.0 molecules/nm 2 for a phosphonic acid terminated ATRP initiator [21]. This confirms that the optimization of reaction conditions can lead to an increase in graft density.…”
Section: Immobilization Of Grafting Agents On Fe 3 O 4 Mnpsmentioning
confidence: 56%
“…Even though not many comparable data are available in the literature on this point, these densities are relatively high comparing to similar studies reported. In particular, Garcia [20], and Babu and Dhamodhran obtained 2.0 molecules/nm 2 for a phosphonic acid terminated ATRP initiator [21]. This confirms that the optimization of reaction conditions can lead to an increase in graft density.…”
Section: Immobilization Of Grafting Agents On Fe 3 O 4 Mnpsmentioning
confidence: 56%
“…One way of testing this hypothesis is to study the grafting density of surface-initiated ATRP, involving monomers with varying rate of propagation. Therefore, we choose to study the grafting density of surface-initiated ATRP involving three different monomers, viz., benzyl methacrylate, styrene, and methyl methacrylate [41]. The results from these study are summarized below.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of magnetite nanoparticles as well as the ATRP initiator, 2-bromo-2-methyl-propionic acid 2-phosphonooxy-ethyl ester ( 1 ) and its anchoring to the magnetite nanoparticle to get ATRP initiator immobilized magnetite nanoparticle ( 2 ) has been reported by us in the literature [41]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations